Toll‐like receptor 4 signalling mediates inflammation in skeletal muscle of patients with chronic kidney disease. Issue 1 (18th October 2016) - Verzola, Daniela; Bonanni, Alice; Sofia, Antonella; Montecucco, Fabrizio; D'Amato, Elena; Cademartori, Valeria; Parodi, Emanuele Luigi; Viazzi, Francesca; Venturelli, Chiara; Brunori, Giuliano; Garibotto, Giacomo
Abstract : Background: Inflammation in skeletal muscle is implicated in the pathogenesis of insulin resistance and cachexia but why uremia up‐regulates pro‐inflammatory cytokines is unknown. Toll‐like receptors (TLRs) regulate locally the innate immune responses, but it is unknown whether in chronic kidney disease (CKD) TLR4 muscle signalling is altered. The aim of the study is to investigate whether in CKD muscle, TLRs had abnormal function and may be involved in transcription of pro‐inflammatory cytokine. Methods: TLR4, phospho‐p65, phospho‐ikBα, tumour necrosis factor (TNF)‐α, phospho p38, Murf 1, and atrogin were studied in skeletal muscle from nondiabetic CKD stage 5 patients ( n = 29) and controls ( n = 14) by immunohistochemistry, western blot, and RT–PCR. Muscle cell cultures (C2C12) exposed to uremic serum were employed to study TLR4 expression (western blot and RT–PCR) and TLR‐driven signalling. TLR4 signalling was abrogated by a small molecule chemical inhibitor or TLR4 siRNA. Phospho AKT and phospho p38 were evaluated by western blot. Results: CKD subjects had elevated TLR4 gene and protein expression. Also expression of NFkB, p38 MAPK and the NFkB‐regulated gene TNF‐α was increased. At multivariate analysis, TLR4 protein content was predicted by eGFR and Subjective Global Assessment, suggesting that the progressive decline in renal function and wasting mediate TLR4 activation. In C2C12, uremic serum increased TLR4 as well as TNF‐α and down‐regulated pAkt. These effects were prevented by blockade of TLR4. Conclusions: CKD promotes muscle inflammation through an up‐regulation of TLR4, which may activate downward inflammatory signals such as TNF‐α and NFkB‐regulated genes.